Antimicrobial Resistance in ESBL-Producing Escherichia coli Isolated from Layer and Pig Farms in Thailand - Nuangmek, Aniroot; Rojanasthien, Suvichai; Chotinun, Suwit; Yamsakul, Panuwat; Tadee, Pakpoom; Thamlikitkul, Visanu; Tansakul, Nattasit; Patchanee, Prapas (Acta Scientiae Veterinariae, 2018)
Background: Study of drug resistance of commensal bacteria in both humans and animals can determine the scale of the drug resistance problem. Usage of antimicrobials to treat infections in humans and animals has generated extensive antimicrobial pressure not only on targeted pathogens but also on commensal bacteria. Commensal Escherichia coli appears to be the major reservoir for resistant genes implicated in the transmission of genetic traits from one bacterium to another. Antimicrobial resistance in Enterobacteriaceae has increased dramatically worldwide in the last decade. An increasing number of community-onset extended-spectrum beta-lactamase (ESBL)-producing bacterial infections, especially those caused by ESBL-producing E. coli, have been reported in many countries, including Thailand. Moreover, ESBL-producing E. coli have been widely detected in food-producing animals and the environment. The increased use of ESBLs in food animals is a serious public health problem. The objective of the study was to determine the prevalence and antimicrobial resistance pattern of ESBL-producing E. coli isolated from pigs, layers, farm workers and stagnant water, in order to increase awareness about antimicrobial usage on farms and to minimize the expansion of the antimicrobial resistance phenomenon in farm settings. Materials, Methods & Results: A total of 588 samples were collected from 107 pig farms and 89 layer farms in Chiang Mai–Lamphun and Chon Buri provinces during May 2015-April 2016. Double-disk diffusion method according to EUCAST (European Committee on Antimicrobial Susceptibility Testing) guidelines was used for detection. The results demonstrated that 36.7% (216/588) of samples were ESBL-producing E. coli-positive, including rectal swabs 74.8% (80/107), pig farm worker stool swabs 57.0% (61/107), stagnant water on pig farms 21.5% (23/107), healthy layer rectal swabs 6.7% (6/89) and layer farm worker stool swabs 51.7% (46/89). Most of the isolates were resistant against ampicillin (99.5%), followed by erythromycin (98.6%) and ceftriaxone (96.3%). All of them were classified as multidrug-resistant strains. Moreover, AMP-CRO-E-TE-C-SXT-CN was the most frequent phenotype pattern detected in animals, humans and the environment, followed by AMP-CRO-E-TE-C-SXT-NA-CN. Discussion: The present study offers clear evidence that the prevalence of ESBL-producing E. coli in healthy pigs is higher than in layers. One possible explanation is that a large amount and variety of antimicrobials are used on pig farms, resulting in a common and significant source of drug-resistant ESBL-producing E. coli. The lower incidence of ESBL-producing E. coli in samples from a pig farm environment than in samples of animal origin indicate that pigs are a reservoir of a reservoir for resistant bacteria and a source of environmental contamination. Antimicrobial resistance patterns of ESBLproducing E. coli detected in all sample types and study locations were quite similar. In almost all ESBL-producing E. coli isolates, resistance was shown against ampicillin, erythromycin, ceftriaxone, tetracycline and chloramphenicol. Moreover, multidrug resistance was found in all isolates of ESBL-producing E. coli. The differences in antimicrobial agent resistance patterns can be used to differentiate sources by employing analytical tools such as discriminant function analysis. A molecular typing protocol is recommended for use in a discriminant function analysis for pattern determination of pathogen spreading. However, genetic fingerprinting techniques for microbial source tracking are more expensive, and facilities with appropriate equipment and expertise are required.